Multi-dimensional ribbon strip-shaped graphene material and preparation method thereof
Through the reaction of liquid Na/K alloy with carbon nanotube material and combined with liquid nitrogen quenching treatment, a multi-dimensional ribbon strip graphene material was prepared, which solved the problem of limited improvement in the performance of sodium ion battery conductors and significantly improved the stability and cycle life of the electrode.
Patent Information
- Application Number
- CN202411856456.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-29
AI Technical Summary
The performance improvement of the conductive agent of existing sodium ion batteries is limited, especially during high-rate charging and discharging and long-term cycles, problems such as increasing electrode polarization and deterioration of the conductive network structure are prone to occur.
The reaction of liquid Na/K alloy and carbon nanotube material and combined with liquid nitrogen quenching treatment, a multi-dimensional ribbon strip graphene material was prepared through the synergistic action of liquid alloy cutting and liquid nitrogen quenching.
It significantly improves the stability and cycle life of the electrode, enhances the stability of the conductive network, reduces the preparation cost, and has good industrial application prospects.
Smart Images

Figure CN119898764A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a multi-dimensional ribbon-shaped graphene material and a preparation method thereof. Background Art
[0002] As an emerging energy storage technology, sodium-ion batteries have attracted much attention due to their abundant raw materials, low cost and strong environmental protection. However, their commercial application faces many challenges, one of which is the problem of battery conductivity. Conductive agents, as an important component of electrode materials, can significantly improve the electronic conductivity of electrodes, thereby improving the specific capacity and cycle performance of batteries. At present, the conductive agents in sodium-ion batteries usually use traditional carbon black (such as Super P) or carbon materials (such as carbon nanotubes, graphite), but the performance improvement of these conductive agents is limited, especially in high-rate charge and discharge and long-term cycle processes, which are prone to problems such as increased electrode polarization and degradation of conductive network structure.
[0003] In recent years, graphene has been considered as an ideal conductive material due to its excellent conductivity, mechanical properties and high specific surface area. However, the traditional graphene preparation method has the following problems:
[0004] Preparation complexity: Chemical stripping requires the use of strong oxidants and reducing agents, which not only increases costs but may also introduce impurities and affect the final material properties.
[0005] Insufficient structural control: It is difficult to precisely control the morphology and dimensions of graphene, so that its conductive properties and specific surface area cannot be fully utilized.
[0006] Application limitations: Single-layer or multi-layer graphene has weak dispersion and conductive network construction capabilities in electrodes and cannot completely replace traditional conductive agents.
[0007] Strip graphene has a unique multi-dimensional structure, which not only has excellent conductivity, but also good dispersibility and high mechanical strength, and can be used as a high-performance conductive material. However, how to prepare strip graphene, especially multi-dimensional strip graphene, through efficient and controllable methods is still a hot topic and difficulty in current research.
[0008] The application of liquid metal in the field of material modification has gradually attracted attention. Its high activity and flexibility give it unique advantages in the cutting and modification of carbon-based materials. However, traditional liquid metal cutting methods have limited control over product morphology and performance, and the preparation process is complicated. In addition, the combination of physical methods (such as liquid nitrogen quenching) to synergistically regulate the structure and properties of materials has not been fully studied. Therefore, developing a new method that combines liquid metal chemical cutting with physical quenching to synergistically enhance the efficiency and prepare strip-shaped graphene conductive agents with multi-dimensional structures is an important way to solve the above problems. Summary of the invention
[0009] In order to overcome the deficiencies in the prior art, the present invention provides a multi-dimensional ribbon-shaped graphene material and a preparation method thereof.
[0010] To achieve the above object, the present invention provides a method for preparing a multi-dimensional ribbon-shaped graphene material, which comprises the following steps:
[0011] S1 Preparation of liquid Na / K alloy: solid sodium and potassium are mixed with ether, ground and mixed, and heated to liquid state. The whole process is carried out under the protection of argon or nitrogen to obtain liquid Na / K alloy;
[0012] S2 Preparation of ribbon-shaped graphene: The carbon nanotube material is magnetically stirred and then transferred to a glove box, freshly distilled 1,2-dimethoxyethane and the liquid Na / K alloy are added to form a suspension for use, the suspension is dispersed by ultrasonic treatment after being sealed with a diaphragm, and the reaction mixture is stirred at room temperature. After stirring, liquid nitrogen is added for quenching; 1-iodoalkane is then added to quench the reaction suspension, and then excess methanol is added until no bubbles are generated to quench any excess Na / K alloy, and the graphene is obtained after filtering, washing, and vacuum drying;
[0013] S3 prepares the battery conductive agent: weighs PVDF as a binder and adds it to NMP to stir and dissolve, then adds the positive / negative electrode material of the sodium ion battery and the ribbon-shaped graphene obtained in step S2, continues stirring for 1 hour to form a uniform suspension, then slurries it on aluminum foil to make sheets, and dries it in an oven at 80°C.
[0014] Preferably, in step S1, the molar ratio of solid sodium to potassium is 0.20-0.25:1, the ratio of the amount of ether added to the total mass of sodium and potassium is 10-15:1, and the heating temperature is 35-50°C.
[0015] Preferably, in step S2, the mass ratio of the amount of carbon nanotubes to the liquid Na / K alloy is 1:150-1:180, the volume ratio of 1,2-dimethoxyethane to the liquid Na / K alloy is 1:100-1:120, the volume ratio of liquid nitrogen to 1,2-dimethoxyethane is 12-10:1, the 1-iodoalkane is selected from one or more of 1-iodopropane, 1-iodobutane, 1-iodopentane and 1-iodohexane, and the mass ratio of 1-iodoalkane to carbon nanotube material is 1.1:-1.5:1.
[0016] Preferably, in step S2, the ultrasonic treatment time is 10-30 min, and the stirring speed is 300-500 rpm.
[0017] Preferably, in step S3, the positive electrode material is NaNi a Mn b Fec O2, 0<a≤1, 0<b≤1, 0<c≤1, a+b+c=1; PVDF: multi-dimensional ribbon-shaped graphite: the mass ratio of positive electrode material is 1:1:8.
[0018] Preferably, the preparation of the positive electrode material comprises the following steps:
[0019] 1) According to the molar ratio of each metal element in the positive electrode material, the nickel source, manganese source and iron source are uniformly ground in a mortar, a certain mass of oxalic acid powder is weighed and placed in deionized water to obtain an oxalic acid solution, and then the metal salt powder is added and stirred at room temperature. The molar ratio of oxalic acid to total metal salt is (1.3-1.1):1; then the mixture is continuously stirred at 80-90° C. for 10-12 hours until the solvent evaporates to obtain a sol, and the obtained sol is dried in an oven at 120° C. for 12 hours to obtain a precursor powder;
[0020] 2) The precursor powder obtained in S1 is mixed evenly with the sodium source in a molar ratio of 1-1.2, the mixing method is ball milling, the time is 3-5h, the ball mill speed is 400-600rpm, and the mixture is placed in a tubular furnace for sintering. Oxygen is passed through the entire sintering process, and the temperature is increased to 800-950°C at a heating rate of 2-5°C / min and kept for 10-18h to obtain the positive electrode material.
[0021] Preferably, the nickel source in step 1) is selected from one or more of nickel oxide, nickel sulfate, nickel chloride, nickel nitrate, nickel acetate, and nickel hydroxide; the manganese source is selected from one or more of manganese oxide, manganese dioxide, manganese nitrate, manganese sulfate, and manganese chloride; the iron source is selected from one or more of iron oxide, iron sulfate, iron chloride, and iron nitrate; and the sodium source in step 2) is selected from one or more of sodium carbonate, sodium bicarbonate, and sodium citrate.
[0022] Preferably, the negative electrode used is a commercial silicon-carbon negative electrode with a diameter of 100 nm.
[0023] The present invention also provides a conductive agent for sodium ion battery materials, which is prepared by using the multi-dimensional strip graphene material prepared by the above method.
[0024] The present invention also provides a sodium ion battery, which is prepared using the product obtained by the above method.
[0025] The beneficial effects of the present invention are as follows:
[0026] Enhanced electrode stability: The synergistic effect of liquid Na / K alloy cutting and liquid nitrogen quenching not only accurately controls the morphology and size of graphene, but also introduces more active sites on the surface of the material, improves the interface stability of the electrode material, and effectively alleviates the problem of increased electrode polarization during charging and discharging.
[0027] Extended cycle life: The multi-dimensional structure of multi-dimensional ribbon-like graphene materials can build a more stable conductive network, reduce the structural degradation of electrode materials during long-term cycles, and significantly improve the cycle life of sodium-ion batteries.
[0028] The process is simple and efficient: the preparation method adopted is simple and highly operable. Through the efficient coordination of liquid alloy and liquid nitrogen quenching, efficient mass production of strip graphene materials is achieved, which significantly reduces the preparation cost and has good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the SEM image of the prepared multi-dimensional strip graphene.
[0030] Figure 2 It is a cycle curve diagram of a battery assembled with the positive electrode material prepared in Example 1 at a current density of 130 mA / g.
[0031] Figure 3 This is a cycle curve of a battery assembled using commercial silicon-carbon negative electrode materials in Example 1 at a current density of 500 mA / g.
[0032] Figure 4 It is a cycle curve diagram of a battery assembled with the positive electrode material prepared in Example 2 at a current density of 130 mA / g.
[0033] Figure 5 This is a cycle curve of a battery assembled using commercial silicon-carbon negative electrode materials in Example 2 at a current density of 500 mA / g.
[0034] Figure 6 It is a cycle curve diagram of a battery assembled with the positive electrode material prepared in Example 3 at a current density of 130 mA / g.
[0035] Figure 7 This is a cycle curve of a battery assembled using commercial silicon-carbon negative electrode materials in Example 3 at a current density of 500 mA / g.
[0036] Figure 8 This is the SEM image of the strip graphene prepared in comparative example 1
[0037] Fig. 9 This is a cycle curve of a battery assembled with the positive electrode material prepared in Comparative Example 1 at a current density of 130 mA / g.
[0038] Fig.10 This is a cycle curve of a battery assembled using commercial silicon-carbon negative electrode materials in Example 1 at a current density of 500 mA / g.
[0039] Fig.11 This is the SEM image of graphene prepared in Comparative Example 2.
[0040] Fig.12 This is a cycle curve of a battery assembled with the positive electrode material prepared in Comparative Example 2 at a current density of 130 mA / g.
[0041] Fig.13 This is a cycle curve of a battery assembled using commercial silicon-carbon negative electrode materials in Example 2 at a current density of 500 mA / g.
[0042] Fig.14 This is the SEM image of the ribbon graphene prepared in Comparative Example 3;
[0043] Fig.15 This is a cycle curve of a battery assembled with the positive electrode material prepared in comparative example 3 at a current density of 130 mA / g.
[0044] Fig.16 This is a cycle curve of a battery assembled using commercial silicon-carbon negative electrode materials in Example 3 at a current density of 500 mA / g.
[0045] Fig.17 This is the SEM image of commercial silicon-carbon negative electrode material.
[0046] Fig.18 This is the XRD pattern of commercial silicon-carbon negative electrode material.
[0047] Fig.19 It is a Raman detection comparison diagram of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0048] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present application will be further described below in conjunction with specific embodiments.
[0049] Example 1
[0050] (1) Using tweezers, solid sodium (0.46 g) and potassium (3.9 g) in a molar ratio of 0.20:1 were mixed with 43.6 ml of ether and placed in a mortar for grinding and mixing for 0.5 h. After mixing, the mixture was transferred to a glass bottle and heated at 40°C until it became liquid. The entire process was carried out in an argon-filled glove box.
[0051] (2) 0.40 g of carbon nanotube material was placed in a 250 mL round-bottom flask equipped with a magnetic stirrer. The container was then transferred to a glove box, where 0.4 ml of freshly distilled 1,2-dimethoxyethane and 40 ml of liquid Na / K alloy were added to form a suspension for later use. The flask was then sealed with a septum and transferred out of the glove box. The suspension was then dispersed by ultrasonic treatment at 40 kHz for 15 min. After ultrasonic treatment, the reaction mixture was stirred at 300 rpm for 3 days at room temperature. After stirring, 4 ml of liquid nitrogen was added twice in equal amounts to avoid internal stress or structural damage to the material that may be caused by rapid cooling. Then 0.44 ml of 1-iodohexane was slowly added through a syringe at a rate of 1 drop / s to quench the reaction suspension. Excess methanol was then added until no bubbles were generated to quench any excess Na / K alloy. Filter, wash, and dry in a vacuum oven at 80°C for 12 h to obtain multidimensional strip graphene.
[0052] (3) According to NaNi 0.33 Fe 0.33 Mn 0.33 The molar ratio of each metal element in the O2 positive electrode material, nickel oxide, manganese dioxide, and iron oxide are uniformly ground in a mortar to obtain metal salt powder. Weigh a certain mass of oxalic acid powder and place it in deionized water to obtain a 0.2 mol / L oxalic acid solution, then add the metal salt powder and stir at room temperature. The molar ratio of oxalic acid to total metal salt is 1.3:1; then continue stirring at 85°C for 10 hours until the solvent evaporates to obtain a sol, and dry the obtained sol in an oven at 120°C for 12 hours to obtain a precursor powder.
[0053] S2. The precursor powder obtained in S1 is evenly mixed with sodium carbonate in a molar ratio of 1.05:1. The mixing method is ball milling. The mixing time is 3 hours. The ball mill speed is 400 rpm. The mixture is placed in a tubular furnace for sintering. Oxygen is passed through the entire sintering process. The temperature is increased to 800°C at a heating rate of 2°C / min and kept at this temperature for 10 hours to obtain the positive electrode material.
[0054] (4) Weigh 0.10 g of polyvinylidene fluoride (PVDF) as a binder and add it to 2000 μL of N-methylpyrrolidone (NMP) and stir to dissolve. Then add 0.80 g of the prepared NaNi 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material and 0.1g multi-dimensional strip graphene conductive agent were stirred for 1 hour to form a uniform suspension. Then the slurry was drawn on aluminum foil and dried in an oven at 80°C.
[0055] (5) In a glove box filled with argon, a CR2032 button cell was assembled with a sodium metal sheet as the counter electrode. The test temperature was 25°C and the voltage range was 2.0-4.0V.
[0056] (6) Weigh 0.10g of polyvinylidene fluoride (PVDF) as a binder and add it to 2000μL of N-methylpyrrolidone (NMP) and stir to dissolve, then add 0.80g of commercial silicon-carbon negative electrode material and 0.1g of multi-dimensional strip graphene conductive agent, and continue stirring for 1h to form a uniform suspension. Then, the slurry is drawn on copper foil to make a sheet and dried in an oven at 80°C.
[0057] (7) In a glove box filled with argon, a CR2032 button cell was assembled using a metal sodium sheet as the counter electrode. The test temperature was 25°C and the voltage range was 0.05-3.0V.
[0058] Figure 1 This is the SEM image of the prepared multi-dimensional strip graphene. It can be seen from the figure that its diameter is about 0.5μm, and it is in the shape of a ribbon or long strip. The surface has irregular wrinkles, showing a corrugated shape. Compared with strip graphene, ribbon-shaped graphene shows higher ID / IG after liquid nitrogen treatment because its surface produces more defects and wrinkles. These defects / wrinkles can provide more reaction sites for sodium ions, resulting in improved battery performance. Fig.19 is the Raman data.
[0059] Figure 2 It is a cycle curve diagram of a battery assembled with the positive electrode material prepared in Example 1 at a current density of 130 mA / g. It can be seen from the figure that after 100 cycles, the battery assembled with the positive electrode material of Example 1 has a specific capacity of 113.3 mAh / g, and a capacity retention rate of 87.0%.
[0060] The particle size of commercial silicon-carbon negative electrode is about 200nm, which is the representative material with the most common commercial use and wide application. Figure 2 It is a cycle curve diagram of a battery assembled using commercial silicon-carbon negative electrode materials in Example 1 at a current density of 500 mA / g. It can be seen from the figure that after 200 cycles, the battery assembled using the commercial silicon-carbon negative electrode materials in Example 1 has a specific capacity of 121.8 mAh / g.
[0061] Example 2
[0062] (1) Using tweezers, solid sodium (0.53 g) and potassium (3.9 g) in a molar ratio of 0.23:1 were mixed with 66.4 ml of ether and placed in a mortar for grinding and mixing for 0.5 h. After mixing, the mixture was transferred to a glass bottle and heated at 45°C until it became liquid. The entire process was carried out in an argon-filled glove box.
[0063] (2) Take 0.40g of carbon nanotube material and put it into a dried 250mL round-bottom flask equipped with a magnetic stirrer. Then transfer the container to a glove box, add 0.54ml of freshly distilled 1,2-dimethoxyethane and 60ml of liquid Na / K alloy to form a suspension for use. Then seal the flask with a septum and transfer it out of the glove box. Then disperse the suspension by ultrasonic treatment for 20min. After ultrasonic treatment, stir the reaction mixture at 400rpm at room temperature for 3 days. After stirring, add 6.5ml of liquid nitrogen, and then slowly add 0.48ml of 1-iodohexane at a rate of 1 drop / s through a syringe to quench the reaction suspension. Then add excess methanol until no bubbles are generated to quench any excess Na / K alloy. Filter, wash, and dry in a vacuum drying oven at 80℃ for 12h to obtain strip graphene.
[0064] (3) According to NaNi 0.33 Fe 0.33 Mn 0.33 The molar ratio of each metal element in the O2 positive electrode material, nickel oxide, manganese dioxide, and iron oxide are uniformly ground in a mortar to obtain metal salt powder. A certain mass of oxalic acid powder is weighed and placed in deionized water to obtain a 0.2 mol / L oxalic acid solution, and then the metal salt powder is added and stirred at room temperature. The molar ratio of oxalic acid to total metal salt is 1.2:1; then continuously stirred at 80°C for 11 hours until the solvent evaporates to obtain a sol, and the obtained sol is dried in an oven at 120°C for 12 hours to obtain a precursor powder.
[0065] S2. The precursor powder obtained in S1 is evenly mixed with sodium carbonate in a molar ratio of 1.1:1, and the mixing method is ball milling. The mixing time is 4 hours, the ball mill speed is 500 rpm, and the mixture is placed in a tubular furnace for sintering. Oxygen is passed through the entire sintering process. The temperature is increased to 850°C at a heating rate of 3°C / min and kept warm for 12 hours to obtain the positive electrode material.
[0066] (4) Weigh 0.10 g of polyvinylidene fluoride (PVDF) as a binder and add it to 2000 μL of N-methylpyrrolidone (NMP) and stir to dissolve. Then add 0.80 g of the prepared NaNi 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material and 0.1g multi-dimensional strip graphene conductive agent were stirred for 1 hour to form a uniform suspension. Then the slurry was drawn on aluminum foil and dried in an oven at 80°C.
[0067] (5) In a glove box filled with argon, a CR2032 button cell was assembled with a sodium metal sheet as the counter electrode. The test temperature was 25°C and the voltage range was 2.0-4.0V.
[0068] (6) Weigh 0.10g of polyvinylidene fluoride (PVDF) as a binder and add it to 2000μL of N-methylpyrrolidone (NMP) and stir to dissolve, then add 0.80g of commercial silicon-carbon negative electrode material and 0.1g of multi-dimensional strip graphene conductive agent, and continue stirring for 1h to form a uniform suspension. Then, the slurry is drawn on copper foil to make a sheet and dried in an oven at 80°C.
[0069] (7) In a glove box filled with argon, a CR2032 button cell was assembled using a metal sodium sheet as the counter electrode. The test temperature was 25°C and the voltage range was 0.05-3.0V.
[0070] Figure 4 It is a cycle curve diagram of a battery assembled with the positive electrode material prepared in Example 2 at a current density of 130 mA / g. It can be seen from the figure that after 100 cycles, the battery assembled with the positive electrode material of Example 2 has a specific capacity of 115.5 mAh / g, and a capacity retention rate of 87.7%.
[0071] Figure 5 It is a cycle curve diagram of a battery assembled using commercial silicon-carbon negative electrode materials in Example 2 at a current density of 500 mA / g. It can be seen from the figure that after 200 cycles, the battery assembled using the commercial silicon-carbon negative electrode materials in Example 2 has a specific capacity of 125.4 mAh / g.
[0072] Example 3
[0073] (1) Use tweezers to mix solid sodium (0.58 g) and potassium (3.9 g) with 67.2 ml of ether in a molar ratio of 0.25:1 and put them into a mortar and grind them for 0.5 h. After mixing, transfer them to a glass bottle and heat them at 50°C until they become liquid. The whole process is carried out in an argon-filled glove box.
[0074] (2) Take 0.40g of carbon nanotube material and put it into a 250mL round-bottom flask with a magnetic stirrer. Then transfer the container to a glove box, add 0.54ml of freshly distilled 1,2-dimethoxyethane and 72ml of liquid Na / K alloy to form a suspension for use. Then seal the flask with a septum and transfer it out of the glove box. Then disperse the suspension by ultrasonic treatment for 30min. After ultrasonic treatment, stir the reaction mixture at 500rpm at room temperature for 3 days. After stirring, add 6.5ml of liquid nitrogen, and then slowly add 0.60ml of 1-iodohexane at a rate of 1 drop / s through a syringe to quench the reaction suspension. Then add excess methanol until no bubbles are generated to quench any excess Na / K alloy. Filter, wash, and dry in a vacuum drying oven at 80℃ for 12h to obtain strip graphene.
[0075] (3) According to NaNi 0.33 Fe 0.33 Mn 0.33The molar ratio of each metal element in the O2 positive electrode material, nickel oxide, manganese dioxide, and iron oxide are uniformly ground in a mortar to obtain metal salt powder. A certain mass of oxalic acid powder is weighed and placed in deionized water to obtain a 0.2 mol / L oxalic acid solution, and then the metal salt powder is added and stirred at room temperature. The molar ratio of oxalic acid to total metal salt is 1.2:1; then continuously stirred at 80°C for 11 hours until the solvent evaporates to obtain a sol, and the obtained sol is dried in an oven at 120°C for 12 hours to obtain a precursor powder.
[0076] S2. The precursor powder obtained in S1 is evenly mixed with sodium carbonate in a molar ratio of 1.2:1, and the mixing method is ball milling. The mixing time is 5 hours and the ball mill speed is 600 rpm. The mixture is placed in a tubular furnace for sintering. Oxygen is passed through the entire sintering process. The temperature is increased to 900°C at a heating rate of 5°C / min and kept at this temperature for 15 hours to obtain the positive electrode material.
[0077] (4) Weigh 0.10 g of polyvinylidene fluoride (PVDF) as a binder and add it to 2000 μL of N-methylpyrrolidone (NMP) and stir to dissolve. Then add 0.80 g of the prepared NaNi 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material and 0.1g multi-dimensional strip graphene conductive agent were stirred for 1 hour to form a uniform suspension. Then the slurry was drawn on aluminum foil and dried in an oven at 80°C.
[0078] (5) In a glove box filled with argon, a CR2032 button cell was assembled with a sodium metal sheet as the counter electrode. The test temperature was 25°C and the voltage range was 2.0-4.0V.
[0079] (6) Weigh 0.10g of polyvinylidene fluoride (PVDF) as a binder and add it to 2000μL of N-methylpyrrolidone (NMP) and stir to dissolve, then add 0.80g of commercial silicon-carbon negative electrode material and 0.1g of multi-dimensional strip graphene conductive agent, and continue stirring for 1h to form a uniform suspension. Then, the slurry is drawn on copper foil to make a sheet and dried in an oven at 80°C.
[0080] (7) In a glove box filled with argon, a CR2032 button cell was assembled using a metal sodium sheet as the counter electrode. The test temperature was 25°C and the voltage range was 0.05-3.0V.
[0081] Figure 6 It is a cycle curve diagram of a battery assembled with the positive electrode material prepared in Example 3 at a current density of 130 mA / g. It can be seen from the figure that after 100 cycles, the battery assembled with the positive electrode material of Example 3 has a specific capacity of 113.6 mAh / g, and a capacity retention rate of 86.6%.
[0082] Figure 7The graph is a cycle curve of a battery assembled with commercial silicon-carbon negative electrode materials in Example 3 at a current density of 500 mA / g. As can be seen from the graph, after 200 cycles, the battery assembled with commercial silicon-carbon negative electrode materials in Example 3 has a specific capacity of 125.1 mAh / g.
[0083] Comparative Example 1
[0084] (1) Use tweezers to mix solid sodium (0.58 g) and potassium (3.9 g) in a molar ratio of 0.25:1 with 67.2 ml of ether in a mortar and grind for 0.5 h. After mixing, transfer to a glass bottle and heat at 35°C until liquid. The whole process is carried out in an argon-filled glove box.
[0085] (2) Take 0.40g of carbon nanotube material and put it into a dried 250mL round-bottom flask equipped with a magnetic stirrer. Then transfer the container to a glove box, add 0.54ml of freshly distilled 1,2-dimethoxyethane and 72ml of liquid Na / K alloy to form a suspension for use. Then seal the flask with a septum and transfer it out of the glove box. Then disperse the suspension by ultrasonic treatment for 30min. After ultrasonic treatment, stir the reaction mixture at 500rpm at room temperature for 3 days. Then slowly add 0.60ml of 1-iodohexane through a syringe at a rate of 1 drop / s to quench the reaction suspension. Then add excess methanol until no bubbles are generated to quench any excess Na / K alloy. Filter, wash, and dry in a vacuum drying oven at 80℃ for 12h to obtain strip graphene.
[0086] (3) According to NaNi 0.33 Fe 0.33 Mn 0.33 The molar ratio of each metal element in the O2 positive electrode material, nickel oxide, manganese dioxide, and iron oxide are uniformly ground in a mortar to obtain metal salt powder. Weigh a certain mass of oxalic acid powder and place it in deionized water to obtain a 0.2 mol / L oxalic acid solution, then add the metal salt powder and stir at room temperature. The molar ratio of oxalic acid to total metal salt is 1.1:1; then continue stirring at 80°C for 12h until the solvent evaporates to obtain a sol, and dry the obtained sol in an oven at 120°C for 12h to obtain a precursor powder.
[0087] S2. The precursor powder obtained in S1 is evenly mixed with sodium carbonate in a molar ratio of 1.1:1, and the mixing method is ball milling. The mixing time is 4 hours, the ball mill speed is 500 rpm, and the mixture is placed in a tubular furnace for sintering. Oxygen is passed through the entire sintering process. The temperature is raised to 950°C at a heating rate of 4°C / min and kept for 18 hours to obtain the positive electrode material.
[0088] (4) Weigh 0.10 g of polyvinylidene fluoride (PVDF) as a binder and add it to 2000 μL of N-methylpyrrolidone (NMP) and stir to dissolve. Then add 0.80 g of the prepared NaNi 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material and 0.1g multi-dimensional strip graphene conductive agent were stirred for 1 hour to form a uniform suspension. Then the slurry was drawn on aluminum foil and dried in an oven at 80°C.
[0089] (5) In a glove box filled with argon, a CR2032 button cell was assembled with a sodium metal sheet as the counter electrode. The test temperature was 25°C and the voltage range was 2.0-4.0V.
[0090] (6) Weigh 0.10g of polyvinylidene fluoride (PVDF) as a binder and add it to 2000μL of N-methylpyrrolidone (NMP) and stir to dissolve, then add 0.80g of commercial silicon-carbon negative electrode material and 0.1g of multi-dimensional strip graphene conductive agent, and continue stirring for 1h to form a uniform suspension. Then, the slurry is drawn on copper foil to make a sheet and dried in an oven at 80°C.
[0091] (7) In a glove box filled with argon, a CR2032 button cell was assembled using a metal sodium sheet as the counter electrode. The test temperature was 25°C and the voltage range was 0.05-3.0V.
[0092] Figure 8 This is the SEM image of the prepared graphene strips. It can be seen from the figure that its diameter is about 0.5μm.
[0093] Fig. 9 It is a cycle curve diagram of a battery assembled with the positive electrode material prepared in Example 1 at a current density of 130 mA / g. It can be seen from the figure that after 100 cycles, the battery assembled with the positive electrode material of Example 1 has a specific capacity of 99.3 mAh / g and a capacity retention rate of 77.5%.
[0094] Fig.10 This is a cycle curve diagram of a battery assembled using commercial silicon-carbon negative electrode materials in Example 1 at a current density of 500 mA / g. It can be seen from the figure that after 200 cycles, the battery assembled using the commercial silicon-carbon negative electrode materials in Example 1 has a specific capacity of 94.1 mAh / g.
[0095] Comparative Example 2
[0096] (1) Take 0.40g of carbon nanotube material and put it into a 250mL round-bottom flask with a magnetic stirrer. Then transfer the container to a glove box, add 0.54ml of freshly distilled 1,2-dimethoxyethane to form a suspension for use. Then seal the flask with a septum and transfer it out of the glove box. Then disperse the suspension by ultrasonic treatment for 30min. After ultrasonic treatment, stir the reaction mixture at 500rpm at room temperature for 3 days. After stirring, add 6.5ml of liquid nitrogen, and then slowly add 0.60ml of 1-iodohexane through a syringe at a rate of 1 drop / s to quench the reaction suspension. Then add excess methanol until no bubbles are generated to quench any excess Na / K alloy. Filter, wash, and dry in a vacuum drying oven at 80℃ for 12h to obtain graphene.
[0097] (3) According to NaNi 0.33 Fe 0.33 Mn 0.33 The molar ratio of each metal element in the O2 positive electrode material, nickel oxide, manganese dioxide, and iron oxide are uniformly ground in a mortar to obtain metal salt powder. Weigh a certain mass of oxalic acid powder and place it in deionized water to obtain a 0.2 mol / L oxalic acid solution, then add the metal salt powder and stir at room temperature. The molar ratio of oxalic acid to total metal salt is 1.2:1; then continue stirring at 90°C for 12h until the solvent evaporates to obtain a sol, and dry the obtained sol in an oven at 120°C for 12h to obtain a precursor powder.
[0098] S2. The precursor powder obtained in S1 is evenly mixed with sodium carbonate in a molar ratio of 1.1:1, and the mixing method is ball milling. The mixing time is 4 hours, the ball mill speed is 500 rpm, and the mixture is placed in a tubular furnace for sintering. Oxygen is passed through the entire sintering process. The temperature is increased to 850°C at a heating rate of 4°C / min and kept for 16 hours to obtain the positive electrode material.
[0099] (4) Weigh 0.10 g of polyvinylidene fluoride (PVDF) as a binder and add it to 2000 μL of N-methylpyrrolidone (NMP) and stir to dissolve. Then add 0.80 g of the prepared NaNi 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material and 0.1g multi-dimensional strip graphene conductive agent were stirred for 1 hour to form a uniform suspension. Then the slurry was drawn on aluminum foil and dried in an oven at 80°C.
[0100] (5) In a glove box filled with argon, a CR2032 button cell was assembled with a sodium metal sheet as the counter electrode. The test temperature was 25°C and the voltage range was 2.0-4.0V.
[0101] (6) Weigh 0.10g of polyvinylidene fluoride (PVDF) as a binder and add it to 2000μL of N-methylpyrrolidone (NMP) and stir to dissolve, then add 0.80g of commercial silicon-carbon negative electrode material and 0.1g of multi-dimensional strip graphene conductive agent, and continue stirring for 1h to form a uniform suspension. Then, the slurry is drawn on copper foil to make a sheet and dried in an oven at 80°C.
[0102] (7) In a glove box filled with argon, a CR2032 button cell was assembled using a metal sodium sheet as the counter electrode. The test temperature was 25°C and the voltage range was 0.05-3.0V.
[0103] Fig.11 is the SEM image of the prepared graphene. Fig.11 It can be seen that due to the lack of liquid alloy cutting, the morphology is the most common flake graphene morphology. The aspect ratio of graphene prepared in Example 1 is about 3:1, and the aspect ratio of Comparative Example 1 is about 10:1. It can be seen that the rapid cooling effect of liquid nitrogen will cause stress concentration in the graphene material along the longitudinal axis. This stress promotes the cleavage and expansion of the material in the transverse direction, forming a wide ribbon structure similar to a ribbon, thereby significantly increasing the width of the material and reducing the aspect ratio.
[0104] Fig.12 It is a cycle curve diagram of the battery assembled with the positive electrode material prepared in Example 2 at a current density of 130 mA / g. It can be seen from the figure that after 100 cycles, the battery assembled with the positive electrode material of Example 2 has a specific capacity of 99.3 mAh / g and a capacity retention rate of 77.5%.
[0105] Fig.13 This is a cycle curve diagram of a battery assembled using commercial silicon-carbon negative electrode materials in Example 2 at a current density of 500 mA / g. It can be seen from the figure that after 200 cycles, the battery assembled using the commercial silicon-carbon negative electrode materials in Example 2 has a specific capacity of 54.1 mAh / g.
[0106] In Comparative Example 2, the obtained graphene sheets are not cut with liquid alloy, and the stacking of the graphene sheets easily forms a bottleneck of electron transmission between the surfaces. Due to the lack of an effective long-range conductive path, the electron transmission efficiency is low. At the same time, the sheet structure is easy to form agglomerations when stacked, resulting in an uneven conductive network, which reduces the overall conductivity and stability of the electrode.
[0107] Comparative Example 3:
[0108] (1) Using tweezers, solid sodium (0.46 g) and potassium (3.9 g) in a molar ratio of 0.20:1 were mixed with 43.6 ml of ether and placed in a mortar for grinding and mixing for 0.5 h. After mixing, the mixture was transferred to a glass bottle and heated at 40°C until it became liquid. The entire process was carried out in an argon-filled glove box.
[0109] (2) 0.40 g of carbon nanotube material was placed in a dried 250 mL round-bottom flask equipped with a magnetic stirrer. The container was then transferred to a glove box, where 0.4 ml of freshly distilled 1,2-dimethoxyethane and 40 ml of liquid Na / K alloy were added to form a suspension for later use. The flask was then sealed with a septum and transferred out of the glove box. The suspension was then dispersed by ultrasonic treatment at 40 kHz for 15 min. After ultrasonic treatment, the reaction mixture was stirred at 300 rpm for 3 days at room temperature. After stirring, 4 ml of liquid nitrogen was added once, and then 0.44 ml of 1-iodohexane was slowly added through a syringe at a rate of 1 drop / s to quench the reaction suspension. Excess methanol was then added until no bubbles were generated to quench any excess Na / K alloy. Filter, wash, and dry in a vacuum drying oven at 80°C for 12 h to obtain multidimensional strip graphene.
[0110] (3) According to NaNi 0.33 Fe 0.33 Mn 0.33 The molar ratio of each metal element in the O2 positive electrode material, nickel oxide, manganese dioxide, and iron oxide are uniformly ground in a mortar to obtain metal salt powder. Weigh a certain mass of oxalic acid powder and place it in deionized water to obtain a 0.2 mol / L oxalic acid solution, then add the metal salt powder and stir at room temperature. The molar ratio of oxalic acid to total metal salt is 1.3:1; then continue stirring at 85°C for 10 hours until the solvent evaporates to obtain a sol, and dry the obtained sol in an oven at 120°C for 12 hours to obtain a precursor powder.
[0111] S2. The precursor powder obtained in S1 is evenly mixed with sodium carbonate in a molar ratio of 1.05:1. The mixing method is ball milling. The mixing time is 3 hours. The ball mill speed is 400 rpm. The mixture is placed in a tubular furnace for sintering. Oxygen is passed through the entire sintering process. The temperature is increased to 800°C at a heating rate of 2°C / min and kept at this temperature for 10 hours to obtain the positive electrode material.
[0112] (4) Weigh 0.10 g of polyvinylidene fluoride (PVDF) as a binder and add it to 2000 μL of N-methylpyrrolidone (NMP) and stir to dissolve. Then add 0.80 g of the prepared NaNi 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material and 0.1g multi-dimensional strip graphene conductive agent were stirred for 1 hour to form a uniform suspension. Then the slurry was drawn on aluminum foil and dried in an oven at 80°C.
[0113] (5) In a glove box filled with argon, a CR2032 button cell was assembled with a sodium metal sheet as the counter electrode. The test temperature was 25°C and the voltage range was 2.0-4.0V.
[0114] (6) Weigh 0.10g of polyvinylidene fluoride (PVDF) as a binder and add it to 2000μL of N-methylpyrrolidone (NMP) and stir to dissolve, then add 0.80g of commercial silicon-carbon negative electrode material and 0.1g of multi-dimensional strip graphene conductive agent, and continue stirring for 1h to form a uniform suspension. Then, the slurry is drawn on copper foil to make a sheet and dried in an oven at 80°C.
[0115] (7) In a glove box filled with argon, a CR2032 button cell was assembled with a sodium metal sheet as the counter electrode. The test temperature was 25°C and the voltage range was 0.05-3.0V.
[0116] Fig.14 This is the SEM image of the prepared ribbon graphene, from which it can be seen that its morphology is destroyed.
[0117] Fig.15 It is a cycle curve diagram of the battery assembled with the positive electrode material prepared in Example 3 at a current density of 130 mA / g. It can be seen from the figure that after 100 cycles, the battery assembled with the positive electrode material of Example 3 has a specific capacity of 90.4 mAh / g and a capacity retention rate of 66.5%.
[0118] Fig.16 This is a cycle curve diagram of a battery assembled using commercial silicon-carbon negative electrode materials in Example 3 at a current density of 500 mA / g. It can be seen from the figure that after 200 cycles, the battery assembled using the commercial silicon-carbon negative electrode materials in Example 3 has a specific capacity of 90.8 mAh / g.
[0119] The present invention relates to a novel method for preparing multi-dimensional strip graphene, which utilizes the reaction of liquid Na / K alloy and carbon nanotube material, and is combined with liquid nitrogen quenching treatment. The liquid alloy cuts the interlayer bonding (such as π-π interaction) and part of the carbon-carbon bond of the graphene strip structure, especially concentrated in the edge area and defect sites. These regional structures are relatively fragile and more easily eroded and broken by liquid metal. Liquid nitrogen applies rapid cooling and mechanical stress to the entire strip graphene structure, and mainly controls the overall morphology and interlayer stacking structure of the strip graphene. Liquid nitrogen quenching induces morphological transformation: the local stress introduced during the liquid alloy cutting process is rapidly released during liquid nitrogen quenching, and the strip structure is locally cracked. Internal stress-induced cracks extend in the lateral direction, gradually changing the strip structure into a ribbon-like shape, achieving fine cutting of the material and a significant increase in active sites.
[0120] This method also provides a new type of conductive agent and its preparation process. The specific steps are as follows: After mixing and grinding solid sodium and potassium with a small amount of ether, they are heated to a liquid state in an inert gas environment to obtain a liquid Na / K alloy. The carbon nanotube material is mixed with freshly distilled 1,2-dimethoxyethane and liquid Na / K alloy, and a uniform suspension is formed by ultrasonic treatment, and then vigorously stirred at room temperature, so that the Na / K alloy cuts the carbon nanotubes through chemical reaction to form a strip structure. After the stirring reaction is completed, liquid nitrogen is added for quenching to quickly freeze the reaction state, further control the size and structure of the strip graphene, and significantly increase the surface active sites and specific surface area of the material. Finally, the reaction is quenched by injecting 1-iodoalkane and methanol, followed by filtration and washing to obtain a multidimensional strip graphene material. In this method, liquid Na / K alloy is used as a reaction medium to decompose carbon nanotube materials into strip graphene through efficient chemical cutting. Its high activity significantly accelerates the reaction process. At the same time, the quenching effect of liquid nitrogen not only controls the cutting depth and morphology, but also increases the active sites and reaction area of graphene by freezing the intermediate reaction structure. The synergistic effect of the two realizes the precise control of multi-dimensional strip graphene and significantly improves the electrochemical performance of the material.
[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a multi-dimensional ribbon-shaped graphene material, characterized in that: The method comprises the following steps: S1 preparing a liquid Na / K alloy: mixing solid sodium and potassium with ether, grinding and mixing, and heating to a liquid state, the whole process being carried out under the protection of argon or nitrogen to obtain a liquid Na / K alloy; S2 Preparation of ribbon-shaped graphene: The carbon nanotube material is magnetically stirred and then transferred to a glove box, freshly distilled 1,2-dimethoxyethane and the liquid Na / K alloy are added to form a suspension for use, the suspension is dispersed by ultrasonic treatment after being sealed with a diaphragm, and the reaction mixture is stirred at room temperature. After stirring, liquid nitrogen is added for quenching; 1-iodoalkane is then added to quench the reaction suspension, and then excess methanol is added until no bubbles are generated to quench any excess Na / K alloy, and the graphene is obtained after filtering, washing, and vacuum drying; S3 prepares the battery conductive agent: weighs PVDF as a binder and adds it to NMP to stir and dissolve, then adds the positive / negative electrode material of the sodium ion battery and the ribbon-shaped graphene obtained in step S2, continues stirring for 1 hour to form a uniform suspension, then slurries it on aluminum foil to make sheets, and dries it in an oven at 80°C.
2. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of solid sodium to potassium is 0.20-0.25:1, the ratio of the amount of ether added to the total mass of sodium and potassium is 10-15:1, and the heating temperature is 35-50°C.
3. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the carbon nanotube to the liquid Na / K alloy is 1:150-1:180, the volume ratio of 1,2-dimethoxyethane to the liquid Na / K alloy is 1:100-1:120, the volume ratio of liquid nitrogen to 1,2-dimethoxyethane is 12-10:1, the 1-iodoalkane is selected from one or more of 1-iodopropane, 1-iodobutane, 1-iodopentane and 1-iodohexane, and the mass ratio of 1-iodoalkane to carbon nanotube material is 1.1:-1.5:
1.
4. The preparation method according to claim 1, characterized in that: In step S2, the ultrasonic treatment time is 10-30 min, and the stirring speed is 300-500 rpm.
5. The preparation method according to claim 1, characterized in that: In step S3, the positive electrode material is NaNi a Mn b Fe c O2, 0<a≤1, 0<b≤1, 0<c≤1, a+b+c=1; The mass ratio of PVDF: multi-dimensional ribbon graphite: positive electrode material is 1:1:
8.
6. The preparation method according to claim 5, characterized in that: The preparation of the positive electrode material comprises the following steps: 1) According to the molar ratio of each metal element in the positive electrode material, the nickel source, manganese source and iron source are uniformly ground in a mortar, a certain mass of oxalic acid powder is weighed and placed in deionized water to obtain an oxalic acid solution, and then the metal salt powder is added and stirred at room temperature. The molar ratio of oxalic acid to the total metal salt is (1.3-1.1):1; then the mixture is continuously stirred at 80-90°C for 10-12h until the solvent evaporates to obtain a sol, and the obtained sol is dried in an oven at 120°C for 12h to obtain a precursor powder; 2) The precursor powder obtained in S1 is uniformly mixed with the sodium source at a molar ratio of 1-1.2, the mixing method is ball milling, the time is 3-5h, the ball milling speed is 400-600rpm, and the mixture is placed in a tubular furnace for sintering. Oxygen is passed through the entire sintering process, and the temperature is increased to 800-950°C at a heating rate of 2-5°C / min and kept warm for 10-18h to obtain the positive electrode material.
7. The method according to claim 6, characterized in that: The nickel source in step 1) is selected from one or more of nickel oxide, nickel sulfate, nickel chloride, nickel nitrate, nickel acetate, and nickel hydroxide; the manganese source is selected from one or more of manganese oxide, manganese dioxide, manganese nitrate, manganese sulfate, and manganese chloride; the iron source is selected from one or more of iron oxide, iron sulfate, iron chloride, and iron nitrate; the sodium source in step 2) is selected from one or more of sodium carbonate, sodium bicarbonate, and sodium citrate.
8. The preparation method according to claim 1, characterized in that: The negative electrode used is a commercial silicon-carbon negative electrode with a diameter of 100nm.
9. A conductive agent for sodium ion battery materials, characterized in that: The multi-dimensional strip graphene material is prepared by the method described in any one of claims 1 to 5.
10. A sodium ion battery, characterized in that: The method is prepared by using the product obtained by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Tentacle-type graphene nanostructure unit, graphene-based composite material with topological structure and preparation method
CN105947973A
Preparation method of graphene nanoribbons
CN106185878A
Graphene nanoribbon material as well as preparation method and application thereof
CN110078060A
Two-dimensional LiV3O8 and graphene composite material as well as preparation method and application thereof
CN111834624A
Three-dimensional strip-shaped graphene compound conductive paste for metal ion battery
CN115241457A